Modulation of extracellular matrix in cancer is associated with enhanced tumor cell targeting by bacteriophage vectors - Yata, Teerapong (Mol Cancer, 2015)
BACKGROUND: Gene therapy has been an attractive paradigm for cancer treatment. However, cancer gene therapy has been challenged by the inherent limitation of vectors that are able to deliver therapeutic genes to tumors specifically and efficiently following systemic administration. Bacteriophage (phage) are viruses that have shown promise for targeted systemic gene delivery. Yet, they are considered poor vectors for gene transfer. Recently, we generated a tumor-targeted phage named adeno-associated virus/phage (AAVP), which is a filamentous phage particle whose genome contains the adeno-associated virus genome. Its effectiveness in delivering therapeutic genes to tumors specifically both in vitro and in vivo has been shown in numerous studies. Despite being a clinically useful vector, a multitude of barriers impede gene transduction to tumor cells. We hypothesized that one such factor is the tumor extracellular matrix (ECM). METHODS: We used a number of tumor cell lines from different species and histological types in 2D monolayers or 3D multicellular tumor spheroid (MCTS) models. To assess whether the ECM is a barrier to tumor cell targeting by AAVP, we depleted the ECM using collagenase, hyaluronidase, or combination of both. We employed multiple techniques to investigate and quantify the effect of ECM depletion on ECM composition (including collagen type I, hyaluronic acid, fibronectin and laminin), and how AAVP adsorption, internalisation, gene expression and therapeutic efficacy are subsequently affected. Data were analyzed using a student’s t test when comparing two groups or one-way ANOVA and post hoc Tukey tests when using more than two groups. RESULTS: We demonstrate that collagenase and hyaluronidase-mediated degradation of tumor ECM affects the composition of collagen, hyaluronic acid and fibronectin. Consequently, AAVP diffusion, internalisation, gene expression and tumor cell killing were enhanced after enzymatic treatment. Our data suggest that enhancement of gene transfer by the AAVP is solely attributed to ECM depletion. We provide substantial evidence that ECM modulation is relevant in clinically applicable settings by using 3D MCTS, which simulates in vivo environments more accurately. CONCLUSION: Our findings suggest that ECM depletion is an effective strategy to enhance the efficiency of viral vector-guided gene therapy.